Pediatric Brain Death Determination - Mathur, Mudit; Ashwal, Stephen (Seminars in Neurology, 2015)
Clinical guidelines for the determination of brain death in children were first published in 1987. These guidelines were revised in 2011 under the auspices of the Society of Critical Care Medicine, the American Academy of Pediatrics, and the Child Neurology Society, and provide the minimum standards that must be satisfied before brain death can be declared in infants and children. After achieving physiologic stability and exclusion of confounders, two examinations including apnea testing separated by an observation period (24 hours for term newborns up to 30 days of age, and 12 hours for infants and children from 31 days up to 18 years) are required to establish brain death. Apnea testing should demonstrate a final arterial PaCO2 20 mm Hg above the baseline and ≥ 60 mm Hg with no respiratory effort during the testing period. Ancillary studies (electroencephalogram and radionuclide cerebral blood flow) are not required to establish brain death and are not a substitute for the neurologic examination. The committee concluded that ancillary studies may be used (1) when components of the examination or apnea testing cannot be completed, (2) if uncertainty about components of the neurologic examination exists, (3) if a medication effect may be present, or (4) to reduce the interexamination observation period. When ancillary studies are used, a second clinical examination and apnea test should still be performed and components that can be completed must remain consistent with brain death.
Keywords: brain death; infants; children; apnea test; ancillary study